Case Report: Near-fatal adverse effects of dopamine agonist for the treatment of restless legs syndrome - Joyce, Jeremiah B.; Patarroyo Rodriquez, Liliana; Sola, Christopher L. (Frontiers in Pharmacology, 2025)
BackgroundThe dopaminergic system plays a central role in motor control, goal-directed behavior, and the pathophysiology of multiple diseases including restless legs syndrome. Dopamine agonists such as pramipexole are commonly prescribed for the treatment of restless legs syndrome; however, growing recognition of potential serious adverse effects has led to updated clinical guidelines which now recommend against the routine use of dopamine agonists as initial therapy.Case PresentationWe present the case of a 64-year-old woman with severe restless legs syndrome and medically unexplained chronic pain who was psychiatrically hospitalized for active suicidal ideation. During her admission, it was discovered that a supratherapeutic dose of pramipexole was the source of iatrogenic harm. Her condition improved following medication taper, appropriate management of restless legs syndrome, and acute psychiatric interventions.ConclusionClinicians should be aware of the potential adverse effects associated with dopamine agonists and adhere to updated recommendations for the management of restless legs syndrome.